Tissue-Specific Biomarker Responses in the Blue Mussel Mytilus spp. Exposed to a Mixture of Microplastics at Environmentally Relevant Concentrations - Revel, Messika; Lagarde, Fabienne; Perrein-Ettajani, Hanane; Bruneau, Mélanie; Akcha, Farida; Sussarellu, Rossana; Rouxel, Julien; Costil, Katherine; Decottignies, Priscilla; Cognie, Bruno; Châtel, Amélie; Mouneyrac, Catherine (Frontiers in Environmental Science, 2019)
The impact of a microplastic (MPs) mixture composed of polyethylene (PE) and polypropylene (PP) plastic particles, prepared from commercially available products, was evaluated in blue mussels Mytilus spp. exposed to three environmentally relevant concentrations: 0.008µg Lˉ¹ (low), 10 µg Lˉ¹ (medium) and 100 µg Lˉ¹ (high). Organisms were exposed for 10 days followed by 10 days of depuration in clean seawater under controlled laboratory conditions. The evaluation of MP effects on mussel clearance rate, tissue structure, antioxidant defences, immune and digestive parameters, and DNA integrity were investigated while the identification of plastic particles in mussel tissues (gills, digestive gland, and remaining tissues), and biodeposits (faeces and pseudofaeces) was performed using infrared microscopy (µFT-IR). Results showed the presence of MPs only in the digestive gland of mussels exposed to the highest tested concentration of MPs with a mean of 0,75 particle/mussel (after the 10 days of exposure). In biodeposits, PE and PP particles were detected following exposure to all tested concentrations confirming the ingestion of MPs by the organisms. A differential response of antioxidant enzyme activities between digestive gland and gills was observed. Significant increases in superoxide dismutase (SOD) and catalase (CAT) activities were measured in the digestive gland of mussels exposed to the low (0.008µg Lˉ¹) and medium (10 µg Lˉ¹) concentrations of MPs and in the gills from mussels exposed to the highest concentration (100 µg Lˉ¹) of MPs that could be indicative of a change in the redox balance. Moreover, an increase in acid phosphatase activity was measured in hemolymph of mussels exposed to 0.008 and 10 µg Lˉ¹ concentrations. No significant difference was observed in the clearance rate, and histopathological parameters between control and exposed mussels. This study brings new insights on the potential sublethal impacts of MPs at environmentally relevant concentrations in marine bivalves.